Wolfram Alpha:
Search by keyword:
Astronomy
Chemistry
Classical Mechanics
Classical Physics
Climate Change
Cosmology
Finance and Accounting
Game Theory
General Relativity
Group Theory
Lagrangian and Hamiltonian Mechanics
Macroeconomics
Mathematics
Microeconomics
Nuclear Physics
Particle Physics
Probability and Statistics
Programming and Computer Science
Quantum Computing
Quantum Field Theory
Quantum Mechanics
Semiconductor Reliability
Solid State Electronics
Special Relativity
Statistical Mechanics
String Theory
Superconductivity
Supersymmetry (SUSY) and Grand Unified Theory (GUT)
The Standard Model
Topology
Units, Constants and Useful Formulas
Basis Oneforms

A oneform is like a machine that when fed with
a vector spits out a number which depends linearly
on the input. We can define dx^{μ} to be the basis
oneform which gives 1 when you input the basis
tangent vector, ∂_{μ}, and 0 when you input ∂_{ν} for
μ ≠ ν. Thus,
[dx^{μ}](∂_{ν}) = (∂/∂x^{ν})(x^{μ}) = ∂x^{μ}/∂x^{ν} = δ^{μ}_{ν}
This should not be interpreted as ∂[∂_{ν}]/∂x^{μ} but
rather as (dx^{μ}) 'acting' on (∂_{ν}).
The basis oneforms are the gradients of the
scalar coordinate functions (i.e. x^{μ} = x^{μ}(p)
where (U,p) is a local chart. Equivalently
we can say φ: U > R^{n} where φ consists of n
real valued functions, x^{μ}). We can show this
as follows:
∇ := (∂/∂x^{ν})e^{ν}
∇x^{μ} = (∂x^{μ}/∂x^{ν})e^{ν}
Where ∂x^{μ}/∂x^{ν} are the components of the gradient
(a dual vector) and e^{ν} are the dual basis vectors.
Therefore,
∇x^{μ} = δ^{μ}_{ν}e^{ν}
= e^{μ}
≡ dx^{μ}
Transformation Laws

vectors oneforms
 
∂_{μ} > ∂'_{μ} = (∂x^{μ}/∂x'^{μ})∂_{μ} dx^{μ} > dx'^{μ} = (∂x'^{μ}/∂x^{μ})dx^{μ}
V^{μ} > V'^{μ} = (∂x'^{μ}/∂x^{μ})V^{μ} ω_{μ} > ω'_{μ} = (∂x^{μ}/∂x'^{μ})ω_{μ}
V'^{x} = (∂x'/∂x)V^{x} + (∂x'/∂y)V^{y}
V'^{y} = (∂y'/∂x)V^{x} + (∂y'/∂y)V^{y}
     
 V'^{x}  =  ∂x'/∂x ∂x'/∂y  V^{x} 
 V'^{y}   ∂y'/∂x ∂y'/∂y  V^{y} 
     
Vector components have a contravariant transformation
law.
∂_{x'} = (∂x/∂x')∂_{x} + (∂y/∂x')∂_{y}
∂_{y'} = (∂x/∂y')∂_{x} + (∂y/∂y')∂_{y}
     
 ∂_{x'} ∂_{y'}  =  ∂_{x} ∂_{y}  ∂x/∂x' ∂x/∂y' 
 _{ }  _{ }  _{ }_{ } ∂y/∂x' ∂y/∂y' 
 
Basis vectors have a covariant transformation law.
∂φ/∂x' = (∂x/∂x')(∂φ/∂x) + (∂y/∂x')(∂φ/∂y)
∂φ/∂y' = (∂x/∂y')(∂φ/∂x) + (∂y/∂y')(∂φ/∂y)
     
 ∂φ/∂x' ∂φ/∂y'  =  ∂φ/∂x ∂φ/∂y  ∂x/∂x' ∂x/∂y' 
     ∂y/∂x' ∂y/∂y' 
 
Oneform components have a covariant transformation
law.
dx' = (∂x'/∂x)dx + (∂x'/∂y)dy
dy' = (∂y'/∂x)dx + (∂y'/∂y)dy
     
 dx'  =  ∂x'/∂x ∂x'/∂y  dx 
 dy'   ∂y'/∂x ∂y'/∂y  dy 
     
Basis oneforms have a contravariant transformation
law.
Oneforms

Oneforms are also known as covariant/dual vectors.
They are often written as ω:
df ≡ ω = ω_{μ}dx^{μ}
Where,
ω_{μ} = {∂f/∂x^{1},∂f/∂x^{2}, ...}
and,
dx^{μ} = {dx^{1},dx^{2}, ...}
Therefore,
df = ω = (∂f/∂x^{1})dx^{1} + (∂f/∂x^{2})dx^{2} ...
= (∂f/∂x^{μ})dx^{μ}
Example: Conversion oneform in polar coorinates to
oneform in xy plane.
x = rcosθ
y = rsinθ
dx = (∂x/∂r)dr + (∂x/∂θ)dθ
dy = (∂y/∂r)dr + (∂y/∂θ)dθ
dx = cosθdr  rsinθdθ
dy = sinθdr + rcosθdθ
Likewise,
dr = (∂r/∂x)dx + (∂r/∂y)dy
dθ = (∂θ/∂x)dx + (∂θ/∂y)dy
∂r/∂x = x/√(x^{2} + y^{2}) = x/r = cosθ
∂r/∂y = y/√(x^{2} + y^{2}) = y/r = sinθ
∂θ/∂x = y/(x^{2} + y^{2}) = y/r^{2} = sinθ/r
∂θ/∂y = x/(x^{2} + y^{2}) = x/r^{2} = cosθ/r
dr = (x/r)dx + (y/r)dy
dθ = (y/r^{2})dx + (x/r^{2})dy
The product of a oneform with a vector is given by:
v = v^{1}(∂/∂x'^{1}) + v^{2}(∂/∂x'^{2}) + ...
= v^{1}∂_{1} + v^{2}∂_{1} + ...
= Σv^{μ}∂_{μ}
^{μ}
ω = ω_{1}dx^{1} + ω_{2}dx^{2} + ...
= Σω_{μ}dx^{μ}
^{ν}
vω = Σv^{μ}∂_{μ}(Σω_{ν}dx^{ν})
^{μ} ^{ν}
= Σv^{μ}ω_{ν}δ^{ν}_{μ}
^{μν}
= Σv^{μ}ω_{μ} ∈ R
^{μ}
Example: Product of vector and oneform in polar
coordinates.
dx = cosθdr  rsinθdθ
dy = sinθdr + rcosθdθ
∂u/∂x = (∂u/∂r)(∂r/∂x) + (∂u/∂θ)(∂θ/∂x)
= cosθ(∂u/∂r)  (1/r)sinθ(∂u/∂θ)
∂u/∂y = (∂u/∂r)(∂r/∂y) + (∂u/∂θ)(∂θ/∂y)
= sinθ(∂u/∂r) + (1/r)cosθ(∂u/∂θ)
(cosθdr  rsinθdθ)(cosθ(∂u/∂r)  (1/r)sinθ(∂u/∂θ))
= cos^{2}θdr(∂u/∂r)  (1/r)cosθsinθdr(∂u/∂θ)
 rsinθcosθdθ(∂u/∂r) + sin^{2}θdθ(∂u/∂θ)
= 1
(sinθdr + rcosθdθ)(sinθ(∂u/∂r) + (1/r)cosθ(∂u/∂θ))
= sin^{2}θdr(∂u/∂r) + (1/r)sinθcosθdr(∂u/∂θ)
 rcosθsinθdθ(∂u/∂r) + cos^{2}θdθ(∂u/∂θ)
= 1
Exterior Derivative

df(V) := Vf
= V^{μ}∂_{μ}f
= (∂f/∂x^{μ})V^{μ}
The reasoning for this can be found by considering
the directional derivative d/dλ = (dx^{μ}/dλ)∂_{μ}.
df[(dx^{μ}/dλ)(∂_{μ})] = df[(dx^{μ}/dλ)(∂/∂x^{μ})]

^ = df[(d/dλ)]

V = (d/dλ)[f]
= df/dλ
In other words, df when given a vector returns
the directional derivative in that direction.
It is worth noting that f is a scalar function
(0form). df is therefore a 1form (dual vector).
Therefore, df acting on the tangent vector dx^{μ}/dλ)(∂_{μ})
produces a scalar, df/dλ.
Example:
f(x,y) = x^{2}y at point (1,1) in the direction (1,1).
= 2xy + x^{2}
= (2,1) at (1,1)
(1,1) => (√2/2,√2/2) after normalization
(2,1).(√2/2,√2/2) = √2/2
^ ^ ^
  
∂f/∂x^{μ} dx^{μ}/dλ df/dλ
= ∂_{μ}f = V^{μ}
In terms of the oneform we get:
df(V) = V^{μ}(∂f/∂x^{μ})
= (∂f/∂x^{μ})V^{μ}
= 2xy(√2/2) + x^{2}(√2/2)
= √2/2 at (1,1) as before.
Infinitesimal Version of the Chain Rule

From before we had:
df(V) = (∂f/∂x^{μ})V^{μ}
Now,
dx^{μ}(V) = dx^{μ}(V^{ν}∂_{ν})
= V^{ν}dx^{μ}(∂_{ν})
= V^{ν}δ^{μ}_{ν}
= V^{μ}
Therefore,
df(V) = (∂f/∂x^{μ})dx^{μ}(V)
Or,
df = (∂f/∂x^{μ})dx^{μ}
In the context of oneforms, dx = (∂x/∂x^{μ})dx^{μ}
is the infinitesimal version of the chain rule.
We can see the relationship as follows:
df/dx^{μ} = (∂f/∂g(x^{μ}))(dg(x^{μ})/dx^{μ}) where f = f(g(x^{μ}))
Therefore, rearranging:
df/dg(x^{μ}) = (∂f/∂x^{μ})(dx^{μ}/dg(x^{μ}))
multiply by dg(x^{μ}) to get:
df = (∂f/∂x^{μ})dx^{μ}
Strictly speaking when we talk about infinitesimal
displacements we should be specifying differential
forms in the equations and not dx^{μ}. This is because
displacement is a scalar that can only be obtained
by contracting a oneform with a tangent vector.
For example, the line segment, ds^{2} = η_{μν}dx^{μ}dx^{ν},
should really be ds^{2} = η_{μν}dx^{μ}dx^{ν}. However, most
references do not distinguish between 'dx', the
informal notion of an infinitesimal displacement,
and 'dx^{μ}', the rigorous notion of a basis oneform
given by the gradient of a coordinate function.
Example:
(ds)^{2} = (dx)^{2} + (dy)^{2}
= ((∂x/∂r)dr + (∂x/∂θ)dθ)^{2} + ((∂y/∂r)dr + (∂y/∂θ)dθ)^{2}
= (cosθdr  rsinθdθ)^{2} + (sinθdr + rcosθdθ)^{2}
= cos^{2}θ(dr)^{2} + r^{2}sin^{2}θ(dθ)^{2} + sin^{2}θ(dr)^{2} + r^{2}cos^{2}θ(dθ)^{2}
= (dr)^{2} + r^{2}(dθ)^{2}